Comparative study between pSWE and 2D-SWE techniques integrated in the same ultrasound machine, with Transient Elastography as the reference method. - Foncea, Camelia; Popescu, Alina; Lupuţoru, Raluca; Fofiu, Renata; Şirli, Roxana; Danilă, Mirela; Sporea, Ioan; Foncea, Camelia Gianina; Lupusoru, Raluca; Sirli, Roxana; Danila, Mirela (Medical Ultrasonography, 2020)
Aim: To evaluate the feasibility of two elastographic methods, point Shear Wave Elastography (pSWE) and two dimensional Shear Wave Elastography (2D-SWE), integrated in the same ultrasound machine, for liver fibrosis (LF) assessment, using Transient Elastography (TE) as the reference method.Material and Methods: We included in the study 115 subjects in which LF was evaluated in the same session by TE (FibroScan, EchoSens), pSWE and 2D-SWE (Samsung-Medison RS85). Reliable liver stiffness (LS) measurements were defined: for TE the median value of 10 measurements with interquartile range (IQR/M)≤30%,while for pSWE and 2D-SWE the median value of 10 measurements, with a reliability measurement index (RMI)≥0.5 and IQR/M≤30%. For classification of LF severity we used TE as the reference method with the following cut-offs: F2≥7kPa, F3≥9.5kPa and F4≥12kPa.Results: Reliable measurements by TE were obtained in 98.2% of cases (113/115), by pSWE in 93.9% of cases (108/115) and by 2D-SWE in 92.1% of cases (106/115), so the final analysis included 101 patients. We divided the cohort into 3 groups: fibrosis 5.9 kPa [AUROC=0.95, 95%CI(0.89;0.98), p<0.0001, Se=94.1%, Sp=89.5%, PPV=82.1%, NPV=96.8%]; F4 LS >8 kPa [AUROC=0.98, 95%CI(0.94;0.99), p<0.0001, Se=94.4%, Sp=95.1%, PPV=81%, NPV=98.7%], while for 2D-SWE they were: F≥2 LS >6.1 kPa [AUROC=0.93, 95%CI(0.86;0.97), p<0.0001, Se=91.1%, Sp=80.6%, PPV=70.5%, NPV=94.7%]; F4 LS >7.6 kPa [AUROC=0.98, 95%CI(0.93;0.99), p<0.0001, Se=100%, Sp=91.5%, PPV=72%, NPV=100%]. We observed strong correlations between LS values obtained by TE and 2D-SWE (r=0.85), between TE and pSWE (r=0.88) and between pSWE and 2D-SWE (r=0.90) (p=0.37), respectively. There were no significant differences between the mean values obtained by pSWE and 2D-SWE (p=0.96).Conclusion: The pSWE and 2D-SWE are feasible methods for assessing liver fibrosis, both techniques strongly correlating with TE results.